Luminescence characteristics of Dy3+doped Gd2O3-CaO-SiO2-B2O3scintillating glasses - J. Kaewkhao (2018)
© 2016 The Chinese Society of Rare Earths. Glasses were prepared from the compositions of 25Gd2O3-10CaO-10SiO2-(55-x)B2O3-xDy2O3(where x is 0.0 mol.%-1.0 mol.%) by the conventional melt-quenching technique at 1400 °C. The results demonstrated the increase in the glass density with respect to the increase in the doping concentrations of Dy2O3. Nine absorption bands were observed. The emission spectra of the developed glass showed two strong peaks at 577 nm (4F9/2→6H13/2) and 482 nm (4F9/2→6H15/2). The highest emission intensity was observed from the developed glass prepared at 0.4 mol.% of Dy2O3, as the efficient energy transfer took place from Gd3+to Dy3+. From the X-ray induced optical luminescence, the emission spectra were identical to those from PL measurements, but with the highest intensity observed from the glass quenched at 0.45 mol.% of Dy2O3. Finally, the integral scintillation efficiency of the developed glass was determined at 27% of that of the commercially available BGO crystal.